Analysis of the Effect of Exports, Imports, Exchange Rates, and Inflation on Indonesia's Economic Growth - Intan Chairani; Septriani Septriani (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to examine the impact of exports, imports, inflation, and exchange rates on economic growth in Indonesia during the period 1993-2022. The analytical method employed is multiple regression analysis. The findings of this research indicate that the variables of imports and exchange rates have a significant positive influence on economic growth. Meanwhile, export variables have a significant negative effect on economic growth. Variable inflation does not have a significant effect on economic growth. So the country needs to develop various types of products that can meet global market demand while looking for opportunities in new markets abroad. And focus on improving the quality and innovation of export products to be essential. This helps ensure that exported products meet high international standards remain competitive in the global market and can boost Indonesia's economic growth. Meanwhile, the government should have the capacity to uphold the level of inflation stability so that it is not higher and causes economic growth to rise.